A Network Device Simulator in Android Platform - Wan Mohd Ghazali, Khadijah; Hassan, Rosilah; Md. Ali, Zulkarnain (2013)
Network device simulator software are used by learners of computer network subject to facilitate learning without using the real network device such as routers, switches and cables. This is done by practicing the commands of network device configuration on the simulator. This paper presents a work in progress on the development of a network device simulator application. As opposed to existing network device simulators that are built for desktops, the simulator that is being developed runs on Android-based mobile devices. The application also utilizes sound educational principle to ensure its effectiveness as a learning aid for computer network learners. The outcome of the work is an Android application that simulates a range of network devices. This application will enable the users to practice configuring network devices anytime anywhere using their mobile devices.